Once Upon a Time: Gender and STEM depictions in Portuguese Children’s Literature - Nunes, A. (3rd International Symposium of Young Researchers in Children’s Literature, organizado pelo Departamento de Línguas e Culturas da Universidade de Aveiro, 2024)
Gender stands as one of the most influential categories in an individual, social and institutional dynamics (Connel, 2002). From the moment a baby is conceived, or perhaps even earlier, distinct narratives begin to form for the soon-to-arrive girl or boy. Expectations regarding physical appearance, psychological traits, educational paths, professional aspirations, and family roles are envisioned as bellies are rubbed and first clothes are lovingly stowed away. In their earliest years, children are confronted with these expectations, which frequently manifest as constraining gender stereotypes: rigid constructs dictating what they are expected to be and to become, whether they are girls or boys. Children’s books are one important vehicle to either reinforce or challenge these expectations and stereotypes. Children connect with characters, with how they are presented, their adventures, the way they solve their problems, challenge their limitations, and succeed. While they are not passive recipients of these potential stereotypes, literature serves as another source of information (Mallan, 2002; Kimmel, 2011) that often perpetuates a binary view of the world, constraining their dreams and aspirations. Science, Technology, Engineering, and Mathematics (STEM) are pivotal fields in today's professional landscape However, despite their significance, children still predominantly envision a white man when asked to draw a scientist (see Thomson et al., 2019). In fact, the participation of women continues to be hindered by gender stereotypes, as young girls often internalize the belief that they will not succeed in these domains (Bian et al.,2017). Research about STEM depictions in picturebooks has shown that there is still room to improve female representation and other marginalize groups’ voices (Cardullo, 2022). Having interest in these matters, a comprehensive sociological, feminist, and literary analysis of gender representativity and stereotypes in STEM depictions in contemporary Portuguese children’s books was conducted, having as a corpus the books recommended by the Portuguese National Reading Plan in the period between 2009 and 2019, as part of a larger doctoral investigation as a PhD researcher in sociology at CIES-ISCTE research center. Utilizing a triangulation strategy (Denzin, 2017) that integrates sociological, feminist, and literary perspectives, the book corpus underwent analysis using a coding grid specifically tailored for this study. Subsequently, a quantitative and qualitative content analysis was conducted, employing a dialectical approach that combined inductive and deductive methods (Taylor, 2003). Both textual, paratextual and visual elements were observed, drawing inspiration from the multimodal perspectives that highlight the importance and interaction of all semiotic modes, specially in picturebooks (Ramos, 2011; Ramos, 2020). Additionally, close reading technique was used, to ensure thorough analysis. Results point out to the underrepresentation of female characters in STEM-related interests, professional options and perceived brilliance. They also underscore the overlapping agency of male characters, even in narratives where female are main characters. Conclusions also reveal the nuanced character of gendered messages, the variation of gender stereotypes and counterstereotypes within the same book, and emphasize the significance of employing gender-reading-lenses and mediation, to fully appreciate the intricacies of children's literature.